Epidemiologic features and management of elbow dislocation with associated fracture in pediatric population. Issue 48 (December 2017) - Lu, Xuemin; Yan, Guisen; Lu, Ming; Guo, Yuan
Abstract : Abstract: This study was conducted to explore epidemiologic features of traumatic elbow dislocation with associated fractures in pediatric population following appropriate treatment options. Incidence of elbow dislocation with associated fractures was analyzed in 67 children using elbow radiographs. Treatment for the displaced elbow joint was performed by closed reduction and proper immobilization. Surgical intervention was applied to restore the correct alignment of the fracture. Mayo Elbow Performance Score (MEPS) was used to measure elbow joint function. Incidence of pure dislocation was observed in 7 of 67 children (10.45%). Elbow dislocation was typically accompanied by a single or multiple fractures in 39 (58.21%) and 21 (31.34%) of 67 children, respectively. In contrast, lateral humeral condyle fracture and medial humeral epicondyle fracture accounted for 35.90% and 30.77% of pediatric elbow fractures. All children with elbow fracture-dislocations received surgical intervention by open reduction and internal fixation. During follow-up, 56% to 92% of children displayed significant recovery of elbow function with improving MEPS after the displaced elbow and fractured fragments were reduced and held in place for weeks. There were statistical differences in MEPS between the types of fractures ( P  < .05 or P  < .01). Incidence of isolated elbow dislocation without fracture is low; rather, it is frequently associated with fractures. Early surgical intervention achieves stable fixation and bony union with utility in improving elbow function in the pediatric population.